Efektivitas Pembelajaran Berbasis Project Based Learning (Pjbl) Serta Pengaruhnya Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Di MA NWDI Lepak - Jumratul Idaini; Muhammad Juaini; Ahmad Baehaki; Amelia Sabira Komala; Aryu Ilham (Universitas Hamzanwadi, 2024)
This study aims to analyze the effectiveness and influence of the Project-Based Learning (PjBL) model on students’ learning outcomes in the Economics subject at MA NWDI Lepak during. The research employed a quantitative method with a Pretest-Posttest Control Group design. Data were collected through tests and observations, then analyzed using the Wilcoxon test, Mann-Whitney test, and the coefficient of determination test. The results showed that the PjBL modeleffectively improved students’ learning outcomes with a significance value of 0.019 (p < 0.05) and had a positive effect on learning outcomes with a significance value of 0.006 (p< 0.05). The contribution of PjBL to learning outcomes was 11.2%, while the remaining percentage was influenced by other factors such as motivation and the learning environment.